The multimedia effect and its stability over time. (August 2015) - Schweppe, Judith; Eitel, Alexander; Rummer, Ralf
Abstract: A central finding in learning with text and pictures is a benefit from learning with combined representations as compared to text only – the multimedia effect. Two experiments (Experiment 1: N = 110; Experiment 2: N = 147) test for whether this advantage is restricted to short-term learning or whether it remains stable when learning is tested after a delay. Subjects learned about a pulley system at their own pace, either with only a written text or with text and a picture of the described pulley system presented simultaneously. We varied whether comprehension and retention were tested immediately after the learning phase or after a delay (1 week later in Experiment 1; 1 week or 2 weeks later in Experiment 2). In both experiments there was a multimedia effect (Experiment 1: η p 2 = .11; Experiment 2: η p 2 = .15) that was independent of the time of testing. These findings suggest that the lack of a pictorial display hindered comprehension of the pulley system's structure substantially and persistently. Highlights: We argue for the importance of delayed tests in studies on multimedia learning. We derive different predictions for the stability of the multimedia effect. Results indicate stable multimedia effect immediately and after delay of 1 and 2 weeks. Processing text only does not serve as a desirable difficulty.